Psychometric Validation of the Workplace Ostracism Scale for Indonesian Generation Z Employees - Shah Hussain; Endang Parahyanti; Muhammad Inzamam Khan (Universitas Muhammadiyah Surakarta, 2026)
Workplace ostracism refers to employees’ perceptions of being ignored, excluded, or avoided by others in the workplace and has been linked to numerous negative psychological and organizational outcomes. Despite the growing presence of Generation Z in the Indonesian workforce, no validated Indonesian-language instrument currently exists to measure workplace ostracism among this population. The present study aimed to translate and validate the 10-item Workplace Ostracism Scale (WOS) for use among Indonesian Generation Z employees. A systematic back-to-back translation procedure was conducted, followed by a readability assessment with Generation Z participants. Data were collected from 198 Indonesian Gen Z employees aged 18- 28 years using snowball and purposive sampling techniques with at least six months of work or internship experience. Exploratory Factor Analysis (EFA) using SPSS 26 and Confirmatory Factor Analysis (CFA) using AMOS 28 were employed to examine the scale’s factor structure, reliability, and validity. Results supported a unidimensional factor structure, with all factor loadings exceeding .50. The scale demonstrated excellent internal consistency (Cronbach’s α = .912; CR = .919) and adequate convergent validity (AVE = .540). Overall model fit indices indicated a good fit. The findings suggest that the Indonesian version of the WOS is a reliable and valid instrument for assessing workplace ostracism among Generation Z employees, providing a valuable tool for both research and organizational practice in Indonesia.